2016
DOI: 10.1116/1.4972210
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of HfO2 using HfCp(NMe2)3 and O2 plasma

Abstract: HfO2 thin films were prepared by plasma-enhanced atomic layer deposition using a cyclopentadienyl-alkylamido precursor [HfCp(NMe2)3, HyALD™] and an O2 plasma over a temperature range of 150–400 °C at a growth per cycle around 1.1 Å/cycle. The high purity of the films was demonstrated by x-ray photoelectron spectroscopy and elastic recoil detection analyses which revealed that by increasing the deposition temperature from 200 to 400 °C, the atomic concentrations of residual carbon and hydrogen reduced from 1.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…Al 2 O 3 due to its polycrystalline nature with more grain boundary defects which leads to easier migration of Cu ions. Different previous reports already have confirmed that crystallization is favorable in case of HfO 2 , compared to Al 2 O 3 for direct deposition on Si[33,34,35,36].…”
mentioning
confidence: 61%
“…Al 2 O 3 due to its polycrystalline nature with more grain boundary defects which leads to easier migration of Cu ions. Different previous reports already have confirmed that crystallization is favorable in case of HfO 2 , compared to Al 2 O 3 for direct deposition on Si[33,34,35,36].…”
mentioning
confidence: 61%
“…ii) Impurity incorporation caused by a higher growth rate may reduce thin film density. [25] Furthermore, it has been reported that the impurity concentration of low temperature ALD thin films is often higher than that of higher temperature ALD thin films. [26] Therefore, while the growth rate of H 2 O-ZnO deposited at 250 °C is higher than that of H 2 O 2 -ZnO deposited at 100 °C, the former has a higher density.…”
Section: Resultsmentioning
confidence: 99%
“…The PMMA was then completely removed by soaking the samples again into acetone. Finally, the fabricated devices were capped with 5/25 nm of thermal ALD AlO x [75] /PE-ALD HfO x , [76] grown at 100 °C (in the FlexAl reactor).…”
Section: Methodsmentioning
confidence: 99%